How forests think : toward an anthropology beyond the human - Kohn, Eduardo (University of California Press, 2013)
Can forests think? Do dogs dream? This book challenges the very foundations of anthropology, calling into question our central assumptions about what it means to be human - and thus distinct from all other life forms. Based on four years of fieldwork among the Runa of Ecuador's Upper Amazon, the book draws on ethnographic research to explore how Amazonians interact with the many creatures that inhabit one of the world's most complex ecosystems.